Molecular Study of Sheep Malignant Theileriosis at Barka Region in the Sultanate of Oman - P Shayan (Iranian Journal of Parasitology, 2011)
Background: We used the PCR technique based on the abovementioned primer pair and sequencing to demonstrate the Theileria infection in the sheep samples collected from Sultanate of Oman.Methods: According to the frame work of "integrated control of ticks and tick borne diseases in globalized world managed by EU-ICTTD-3 project, the samples from blood, liver, spleen, lymph node and lung were sent to the laboratory of Iranian Research Center for Ticks and Tick-borne Diseases (IRCTTD). Samples from blood smear and impression smears from liver, spleen, lymph node, and lung were analyzed by Geimsa staining. The DNA was extracted from the abovementioned samples and analyzed by PCR technique using specific primers derived from the nucleotide sequences of 18S rRNA gene of T. lestoquardi, which can amplify the common region in other Theileria and Babesia spp. Subsequently the amplified DNA was sequenced.Results: The analysis of blood smears of the sheep was negative for piroplasmosis performed through the Giemsa staining. The impression smears prepared from liver, spleen, lymph node, and lung showed suspicious structures mimicking Theileria schizonts in some cells. The results showed an expected PCR product of 428 bp in length, which is specific for Theileria spp. The PCR products were subsequently sequenced. The corresponding nucleotide sequence is registered under accession number JF309152 in GenBank. The sequence alignment in GenBank showed that the PCR products had 99% homology to the known T. lestoquardi registered under accession number AF081135 in the GenBank. Conclusion: Oman sheep are highly susceptible for Theileria infection and the infected sheep mostly die before the microschizonts or erythrocytic form of Theileria appears in the nucleated or erytrocytic cells respectively.